Identification of Critical Target Protein for Cystic Fibrosis using Systems Biology Network Approach - Tammanna R. Sahrawat; Sherry Bhalla (International Journal Bioautomation, 2013)
The most critical step in drug discovery process is target identification. Loss of function disease such as cystic fibrosis is caused by impairment of one protein and target identification of such diseases becomes a more tedious task. Protein interactions can provide an insight of other proteins which could be targeted to affect the regulation of particular protein involved in disease. The present study was taken to identify the critical protein which could be targeted to affect the regulation of CFTR (Cystic Fibrosis Transmembrane Regulator) which is mutated in Cystic Fibrosis using a systems biology network approach involving STRING and ClusterONE plugin of Cytoscape. Five proteins namely PDZK1, SLC9A3R1, CFTR, CANX and HSPA8 were identified to be the critical proteins which could affect the regulation of CFTR. Calnexin (CANX) and HSPA8/HSC70 were also present in Cluster 2 obtained by ClusterONE which contains proteins responsible for degradation of misfolded protein. Finally HSPA8/HSC70 was selected to be a probable critical target protein as it has been reported that abolishing the interaction of F508del-CFTR with calnexin (CAS treatment) has no major (positive or negative) effect on ERAD of F508del-CFTR. Thus, systems biology approach may hold great promise to identify probable therapeutic targets.